2017
DOI: 10.14238/pi57.1.2017.47-51
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of axillary and tympanic membrane to rectal temperatures in children

Abstract: (AUC 0.903 and 0.903, respectively). Conclusion Axillary temperature measurement is as good as tympanic membrane temperature measurement and can be used in daily clinical practice or at home. By increasing the optimum fever cut-off point for axillary and tympanic membrane temperature to 37.8oC, we find sensitivity 81% and 88%, specificity 86% and 73%, PPV 95% and 91%, and NPV 95% and 91%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…The cut-off points were various. Among the included articles, 7 [5,8,18,[33][34][35][36] studies set the optimal cut-off and the other 5 [3,13,14,20,21] studies analyzed the diagnostic test accuracy of tympanic thermometry under different cut-offs. The range of the cutoff point was from 37.0℃ to 38.0℃.…”
Section: Accuracy Of Tympanic Thermometry In Children Under Differentmentioning
confidence: 99%
“…The cut-off points were various. Among the included articles, 7 [5,8,18,[33][34][35][36] studies set the optimal cut-off and the other 5 [3,13,14,20,21] studies analyzed the diagnostic test accuracy of tympanic thermometry under different cut-offs. The range of the cutoff point was from 37.0℃ to 38.0℃.…”
Section: Accuracy Of Tympanic Thermometry In Children Under Differentmentioning
confidence: 99%
“…The cut-off points were various. Among the included articles, 7 [5,8,18,[33][34][35][36] studies set the optimal cut-off and the other 5 [3,13,14,20,21] studies analyzed the diagnostic test accuracy of tympanic thermometry under different cut-offs. The range of the cutoff point was from 37.0℃ to 38.0℃.…”
Section: Accuracy Of Tympanic Thermometry In Children Under Differentmentioning
confidence: 99%
“…There was only one study [20] reported diagnostic test accuracy under the cut-off 37.4℃. In this study, for ear temperature (37.4°C), sensitivity, specificity, PPV, and NPV were 0.96, 0.36, 0.82, and 0.73 respectively.…”
Section: Accuracy Under the Cut-off Of 374℃mentioning
confidence: 99%
See 2 more Smart Citations